Current Trends to Obtain Metals and Alloys with Ultrafine-Grained Structure - A. B. Naizabekov, A. S. Kolesnikov, M. A. Latypova, T. D. Fedorova, and A. D. Mamitova (Успехи физики металлов, 2022)
Obtaining materials with improved and properly balanced physical and mechanical properties remains one of the main goals of materials science. At the same time, one of the most promising ways to improve the properties of metallic materials without changing and complicating their chemical and phase compositions is to obtain ultrafine-grained states within them. Such materials are characterized by high strength and high ductility. This combination of properties is crucially important for responsible products, where the weight and size of the part are important. For example, for medical implants, which, at maintaining strength, can be made thinner, and, if the load is exceeded, it will not be broken, damaging the surrounding tissues, but will only bend and can be subsequently replaced. Such a combination of strength and ductility is difficult to be obtained by other methods (e.g., heat treatment). However, for the bulk ultrafine-grained materials, in addition to the requirements for grain size, there are also requirements for the isotropism and equiaxiality of grains, the misorientation boundaries of which should be predominantly high-angle. Traditional deformation technologies (such as drawing and cold rolling) are also accompanied by structure refinement. However, in general, the substructure has a cellular character with grains elongated in the direction of drawing or rolling and contains a high proportion of low-angle boundaries. This fact contributes to the anisotropy of the properties of products in the absence of a combination of properties of high strength and ductility at the same time. Over the past 2–3 decades, the technologies of severe plastic deformation (SPD) have attracted great interest in the production of ultrafine-grained materials. However, the growth in demand is significantly limited by the high cost of manufacturing products from such materials due to the high energy and labour intensity of their production. Therefore, this article reviews and analyses contemporary technologies for the production of metals and alloys with ultrafine-grained structure, combining both high strength and ductility, by using relatively simple and inexpensive devices, which allow spending the minimum possible amount of time in the manufacture of products. The literature overview shows the level of the process to develop technology for obtaining the ultrafine-grained structure in metals and alloys. Such structures provide a combination of a high level of strength characteristics with high ductility that fundamentally distinguishes such materials from conventional ones. This is urgent for applications, where the weight, size, or special exploitation properties of the part are crucially important.